Simulation of Soil Water and Salt Balance in Three Water-Saving Irrigation Technologies with HYDRUS-2D - Yanhui Jia; Wei Gao; Xiulu Sun; Yayang Feng (Agronomy, 2023)
Mulch drip irrigation (MDI) technology can effectively solve the problem of insufficient temperature accumulation during the pre-fertility period and facilitate the efficient supplementation of water and fertilizer during the fertility period in spring corn planting. Moreover, this local MDI technology also has impacts on the farmland environment. To investigate the effect of drip irrigation technology on the water and salt environment of farmland, a field study on corn cultivation was carried out at West Liaohe Plain. In addition, the water and salt dynamics of the farmland were simulated using HYDRUS-2D for mulch drip irrigation (MDI), shallowly buried drip irrigation (SBDI), and sprinkler irrigation (SI), with variable rainfall and initial salt content. The results showed that the distribution of and variation in water and salt in the soil were similar under MDI and SBDI. The change near the drip tape was mainly affected by irrigation, while the water and salt in the soil between drip tapes were correlated with irrigation and rainfall. The amount of salt in the topsoil (5 cm) increased with a decrease in rainfall. With an initial EC = 480 μs/cm (soil salt content 0.1%), the salinity of the topsoil under MDI was significantly higher than that under SBDI and SI within two years. The topsoil salinity was similar for all three irrigation technologies with increasing operating life, reaching a relatively stable state, and much lower than the salinity determination threshold of 480 μs/cm. Given the current conditions of rainfall, soil, buried depth, and mineralization in the West Liaohe Plain, the risk of secondary salinization is minimal if irrigation management is reasonable. This study provides data to support the application of drip irrigation technology in the Western Liaohe Plain.